The impact of RS–040 highway on wildlife roadkill patterns, Porto Alegre, Southern Brazil - Zanettini Tres, Gabrielle; Dominguez Pacheco, Tiago; Cardozo Silva, Vitor Gabriel; Carniel Wagner, Paulo Guilherme; Nisa-Castro-Neto, Walter; Farias Cruz, Cláudio Estêvão (Ethnobiology and Conservation, 2024)
Road infrastructure has caused severe impacts on the environment and wildlife. Understanding and mitigating these effects are essential conservation measures. This study aimed to evaluate wildlife mortality due to animal-vehicle collisions along an 80-km stretch of the Tapir Rocha Highway (RS–040). The field inventory was carried out between August 2015 and March 2019. Once a week, two observers drove along the highway at an average speed of 40 km/h and all the vertebrate roadkill spotted from the car were assessed to record the species, carcass condition, and the roadkill locations along the road. In total, 2,371 dead animals were recorded and categorized into 137 species. The most affected classes were mammals (n = 1,223), and birds (n = 704). The most affected wild species were white-eared opossums (Didelphis albiventris, n = 559), black-and-white tegus (Salvator merianae, n = 129), and coypus (Myocastor coypus, n = 102). Carcass exposure assessments indicated that many (n = 637) of the animal deaths occurred the night before our arrival, which may suggest that nocturnal species were among the most vulnerable to mortality. Roadkill sighting peaked in the spring (34%) and summer (25%), probably due to reproductive activity and juvenile dispersal. Evident seasonal variations included a 50% reduction in reptile roadkill rates in autumn-winter compared to spring-summer, and a 20-percentage-point increase in the number of mammal road deaths in the winter. The reduced activity that reptiles display at low temperatures, and seasonal changes in carnivore food habits may explain these respective findings. While most of the animal victims of roadkill were common and widely distributed species with abundant populations, decreasing abundance of these species is a growing conservation concern.